Image-fiction as an action strategy for possible worlds (Palíndromo, 2020)
In this article, an application of the theories of possible worlds in the study of the image and its effects is proposed. After a brief introduction to this theoretical universe, we move on to the context of visual arts, in which there are not many published works on the subject. A notion of “ways of worldmaking” is developed, which emerges from an active image-fiction, established by the “fingere” of the artist. The attitude of self-denunciation of this image allows the viewer to find evidence of its manipulated quality, which ultimately allows for a cognitive change in relation to the constructions and changes that we can make in our so-called real world. After a case study, it is concluded that, like the image, reality is a manipulable matter, and the understanding of this opens up paths for the construction of new contexts in the present.
Keywords: possible worlds; image-fiction; fingere; contemporary art; image theory